Sosialisasi Cuci Tangan dan Pemberdayaan Masyarakat sebagai Upaya Pencegahan Peningkatan Covid 19 di Desa Danguran Klaten Selatan - Makhabbah Jamilatun; Retno Wulandari; Meliniya Santi Khoirunisa (Abdimas Mandalika, 2023)
Abstract: Hand washing is one way to prevent the transmission of Covid-19 and other infectious diseases. Based on the results of observations that have been made, there are still some residents in Danguran Klaten Selatan Village who have not paid much attention to the dangers of the Covid-19 virus, some residents have still not implemented health protocols such as washing their hands. Thus, it is necessary to socialize and empower the community in Danguran Klaten Selatan Village. The purpose of community service activities is to increase the knowledge and understanding of residents in Danguran Klaten Selatan Village about the importance of washing hands as an effort to prevent the transmission of Covid-19. The method of implementing this community service activity is socialization and education through mentoring and counseling on the main and supporting activity programs. Community service activities are carried out through several stages. First, a target group survey was conducted. Second, identify the need for community service activities. Third, preparation of the facilities and infrastructure needed for community service activities. Fourth, the implementation of community service activities. The results of community service activities are that residents of Danguran Klaten Selatan Village gain knowledge, understanding, and experience regarding preventive measures against Covid-19.Abstrak: Cuci tangan merupakan salah satu cara mencegah penularan Covid-19 dan penyakit menular lainnya. Berdasarkan hasil observasi yang telah dilakukan, masih ada beberapa warga di Desa Danguran Klaten Selatan belum terlalu memperhatikan bahaya virus Covid-19, beberapa warga masih belum menerapkan protokol kesehatan seperti mencuci tangan. Dengan demikian, perlu adanya sosialisasi dan pemberdayaan masyarakat di Desa Danguran Klaten Selatan. Tujuan kegiatan pengabdian masyarakat untuk meningkatkan pengetahuan dan pemahaman warga di Desa Danguran Klaten Selatan tentang pentingnya mencuci tangan sebagai upaya pencegahan penularan Covid-19. Metode pelaksanaan kegiatan pengabdian masyarakat ini adalah sosialisasi dan edukasi melalui pendampingan dan penyuluhan program kegiatan utama dan pendukung. Kegiatan pengabdian dilakukan melalui beberapa tahapan. Pertama, dilakukan survei kelompok sasaran. Kedua, identifikasi kebutuhan kegiatan pengabdian. Ketiga, persiapan sarana dan prasarana yang diperlukan dalam kegiatan pengabdian. Keempat, pelaksanaan kegiatan pengabdian. Hasil kegiatan pengabdian masyarakat adalah warga Desa Danguran Klaten Selatan mendapatkan pengetahuan, pemahaman, dan pengalaman mengenai tindakan pencegahan terhadap Covid-19.